Stimulating the regenerative capacity of the human retina with proneural transcription factors in 3D cultures - Juliette Wohlschlegel; Faith Kierney; Kayla L. Arakelian; Guillaume Luxardi; Naran Suvarnpradip; Dawn Hoffer; Fred Rieke; Ala Moshiri; Thomas A. Reh (Proceedings of the National Academy of Sciences, 2025)
Retinal diseases often lead to degeneration of specific retinal cell types with currently limited therapeutic options to replace the lost neurons. Previous studies have reported that overexpression of ASCL1 or combinations of proneural factors in Müller glia (MG) induce regeneration of functional neurons in the adult mouse retina. Recently, we applied the same strategy in dissociated cultures of fetal human MG and although we stimulated neurogenesis from MG, our effect in 2D cultures was modest and our analysis of newborn neurons was limited. In this study, we aimed to improve our MG reprogramming strategy in a more intact retinal environment. For this purpose, we used an in vitro culture system of human fetal retinal tissue and adult human postmortem retina. To stimulate reprogramming, we used lentiviral vectors to deliver constructs with a glial-specific promoter (HES1) driving ASCL1 alone or in combination with additional developmental transcription factors (TFs) such as ATOH1 and NEUROD1 . Combining IHC, scRNA-seq, and electrophysiology, we show that human MG can generate new neurons even in adults. This work constitutes a key step toward a future clinical application of this regenerative medicine approach for retinal degenerative disorders.